Un ejemplo de reelaboración de un cuento de animales en dos novelas picarescas (Alonso, mozo de muchos amos y Lazarillo de Manzanares) - Arciello, Daniele (Edad de oro, 2020)
The key characteristic of Seventeenth century literature was the binding connection between oral tradition and written production. The two elements gave birth to what is currently considered as one of the most significant cultural prosperity age for Spain. Taking into account these considerations, the present article proposes to analyse the re-elaboration of a folkloric animal tale in two works attributed to the picaresque genre. After a review of the central aspects of protagonists’ personality in the novels in question, it will be highlighted each author’s personal contributions, as a result of the remodelling of the tale, subjugated to their ethic-literary intentions.